2019
DOI: 10.3892/mmr.2019.10822
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin metabolites 2,3‑DHBA and 2,5‑DHBA inhibit cancer cell growth: Implications in colorectal cancer prevention

Abstract: Although compelling evidence exists on the ability of aspirin to treat colorectal cancer (CRC), and numerous theories and targets have been proposed, a consensus has not been reached regarding its mechanism of action. In this regard, a relatively unexplored area is the role played by aspirin metabolites 2,3-dihydroxybenzoic acid (2,3-DHBA) and 2,5-dihydroxybenzoic acid (2,5-DHBA) in its chemopreventive actions. In a previous study, we demonstrated that 2,3-DHBA and 2,5-DHBA inhibited CDK1 enzyme activity in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…3-(3-hydroxyphenyl)propionic acid and dihydrocaffeic acid are respectively the dehydroxylated and hydrogenated forms of caffeic acid (a common dietary component found in a variety of plant-derived food products) by gut microbiota (Bifidobacterium, Escherichia, Lactobacillus, and Clostridium) and merit attention for their antioxidant activities [103][104][105][106]. Gentisic acid, an active microbial metabolite of salicylic acid hydroxylation, is shown to inhibit colorectal cancer cell growth [52]. Some dietary phytochemicals such as ferulic/isoferulic acid and vanillic acid may be metabolized by gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…3-(3-hydroxyphenyl)propionic acid and dihydrocaffeic acid are respectively the dehydroxylated and hydrogenated forms of caffeic acid (a common dietary component found in a variety of plant-derived food products) by gut microbiota (Bifidobacterium, Escherichia, Lactobacillus, and Clostridium) and merit attention for their antioxidant activities [103][104][105][106]. Gentisic acid, an active microbial metabolite of salicylic acid hydroxylation, is shown to inhibit colorectal cancer cell growth [52]. Some dietary phytochemicals such as ferulic/isoferulic acid and vanillic acid may be metabolized by gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…OCTNs seem to be a factor in tumor progression; however, it remains to be investigated whether modulation of OCTN activity in cancer is a valid approach for growth repression, especially when considering their function in the organism. In this context, it seems noteworthy that there are reports linking the salicylic acid metabolites and their influence on cyclin-dependent kinases to colorectal cancer prevention by aspirin [181,182]. Moreover, a metabolomics analysis of mucosal biopsies obtained from individuals with an approximately three-year treatment with aspirin revealed an influence on carnitine shuttle metabolism [183].…”
Section: Organic Cation Transporter Novel Type (Octns)mentioning
confidence: 98%
“…Studies carried out in our laboratory have demonstrated that aspirin metabolites 2,3-DHBA and 2,5-DHBA are capable of inhibiting Cyclin Dependent Kinase (CDK) enzyme activity and cancer cell growth, suggesting their potential role in CRC prevention [62,63]. Our study also demonstrated that 2,5-DHBA was effective in inhibiting cell proliferation in HCT-116 and HT-29 cells [63]. It is important to note that HCT-116 cells do not express COX-2 and HT-29 cells have inactive COX-2 [64], indicating that a COX-independent mechanism is at play.…”
Section: Hbas Of Aspirin and Flavonoid Origin Exhibit Anti-proliferatmentioning
confidence: 99%
“…Hence, upon consumption of an 81 mg aspirin tablet, its concentration in the gut will be in the range of 0.3 mM to 1.4 mM under fed (~750 mL GI volume) and fasting (~160 mL GI volume) conditions, respectively [73]. It is important to note that not all HBAs are effective, as 4-HBA, 2,4-DHBA and 2,6-DHBA failed to inhibit cancer cell growth, suggesting that HBAs are selective in their modes of action [57,63]. It is also crucial to highlight the role of transporters in the uptake of these HBAs.…”
Section: Hbas Of Aspirin and Flavonoid Origin Exhibit Anti-proliferatmentioning
confidence: 99%
See 1 more Smart Citation